Market mind games : a radical psychology of investing, trading, and risk - Shull, Denise (McGraw Hill-Ascent Audio, 2012)
Seize the advantage in every risk decision with the most misunderstood asset you have-human emotion What if the mystery of market crashes stems from a simple but total misunderstanding of our own minds? Could everything we think we know about ourselves-intelligence and rationality versus emotion and irrationality-be wildly off the mark? Simply put: yes. With these words, Denise Shull introduces her radical-and supremely rational-approach to risk. Her vision stems from the indisputable fact that human beings can't make any decision at all without emotion and that emotion gets the first-and last-word when it comes to our perceptions and judgments. Shull should know. She started out managing major accounts for IBM and then chose to research unconscious emotional patterns instead of getting her MBA. Next she became a trader and trading desk manager while continuing to study biopsychology. We are all taught that sidelining our emotions is the best way to make good decisions-Shull declares the converse: emotions inform us. Attempting to control them actually increases the risks we take. Shull advocates treating feelings as data, and she convincingly argues that doing so eradicates the baffling question that repeats itself in our heads after making a poor investing decision: "What was I thinking?" Through a series of "lectures," Shull logically but engagingly connects emotions, beliefs, and context to our innate reaction to uncertainty and risk (yes, the two are different). In Market Mind Games, she merges more than 20 years of studying risk decisions into a single, astoundingly effective strategy. A reasonable approach to emotion is the best and only way to win the investing game. The methods Shull details in Market Mind Games shake the foundation of conventional market and decision psychology. And, most important, they work.